Flow Visualization Study Of Water Tunnel For Micro-Hydrokinetic Turbine Application - Teo, Chen Lung (Universiti Sains Malaysia, 2019)
The use of flow visualization often plays a defining role in the understanding of many fluid flow problems. The purpose of this research is to establish an experimental set-up for flow visualization study of micro-hydrokinetic turbine in water tunnel and to investigate the flow behaviour around a micro-hydrokinetic turbine. Dye injection method was used as the flow visualization technique in this research. The dye mixtures consisted of dye with water, dye with milk, dye with ethanol, and milk. Each mixture has different ratio combination, the combination of ratio tested were 1:9, 3:7 and 5:5 for dye-water; 1:5:4, 3:3:4 and 5:1:4 for dye-water-milk; 3:6:1 and 3:6.5:0.5 for dye-water-ethanol. All these solutions were being investigated in different flow regimes such as the static flow, and dynamic flow at 46rpm, 176rpm, and 864rpm. These mixtures were tested and analysed in terms of clarity of the image and video taken, rate of dispersion in water, and the flow path line of the dye upon released from the dye ejector to find out the best type of mixture and combination ratios in different flow regimes. The experimental set-up is a simple, low-cost, and feasible set-up with the aid of the gravity-feed system. The experimental set-up was performed on a water tunnel with a savonius turbine. A savonius turbine model for hydrokinetic application was placed in the test section of the water tunnel to visualize and study the flow behaviour around the model. Dye-water (3:7) added with alcohol (ethanol) gives the best solution for flow visualization study in static flow. The alcohol (ethanol) added gives a straight path line to the dye so that successful interpretation of fluid flow can be performed accurately. While milk, dye-water, and dye-water-milk mixtures showed a downward curve movement once ejected from the ejector V due to their density being higher than water, in other words, they are not neutrally buoyant. Thus, a straight path line could not be obtained, which concluded that they were not applicable in the static flow condition. In dynamic flow at 46rpm, dye-water (1:9) gives the best clarity in terms of flow pattern observation around the turbine. It did not dissolve quickly at this speed and there was no concentrated spot in the dye region. However, the turbine has to be placed closer to the ejector (6cm) to get a straight dye path line. In dynamic flow at 176rpm, all dye solutions without milk started to dissolve quickly once ejected. The dye-water-milk (3:3:4) was the best solution because milk prolonged the diffusion of dye at this speed, keeping the flow pattern visible by retaining the dye traces in the water, the fat content in the milk helps to retard the diffusion of dye. In dynamic high-speed flow at 864rpm, the effect of milk in prolonging the diffusion of dye became more significant, the best solution was dye-water-milk (5:1:4). Hence, all types of mixtures behave differently in different flow regime. Some mixture might perform well in certain flow regime, but not necessary the other.